Depression, Anxiety, and Post-traumatic Stress Disorder Following a Hypertensive Disorder of Pregnancy: A Narrative Literature Review - Roberts, Lynne; Davis, Greg K.; Homer, Caroline S. E. (Frontiers in Cardiovascular Medicine, 2019)
Introduction Pregnancy and childbirth can be a source of anxiety and worry for women. This is probably more so for women with a complicated pregnancy. Anxiety and worry may contribute to, or exacerbate, mental health disorders including depression and post-traumatic stress disorder (PTSD). Mental health is an integral part of health and well-being and poor mental health can be detrimental to the woman’s welfare and her infant’s behaviour and cognitive development. It may be undetected, potentially leading to a burden on the woman, her family, the health system and society. Women with complicated pregnancies, such as those with hypertensive disorders of pregnancy (HDP), may be at greater risk of poor mental health. The aim of this review was to examine whether there is an association between depression, anxiety and PTSD in postpartum women with a history of HDP. Methods A narrative literature review was undertaken. Using the key search terms: preeclampsia, gestational hypertension, hypertensive disorders, pregnancy complications, depression, anxiety and post-traumatic stress disorder; electronic databases were searched to determine what is known about depression, anxiety and PTSD after HDP. Results In total, 17 publications were included. The relationship between HDP and depression, anxiety and PTSD was variable between studies and inconsistent. Although some studies reported no significant association, there is a trend for increased prevalence and symptom severity of depression, anxiety and PTSD following HDP. This trend was particularly evident following the more severe presentations of HDP. It was uncertain whether this association was due to the hypertensive disorder itself, the sequelae of the HDP, such as giving birth to a preterm baby, or it predated the pregnancy. Conclusions Women who experience HDP may be at increased risk of developing postpartum depression, anxiety and PTSD. Awareness of, and screening for, these mental health disorders in the postpartum period will alert clinicians to the need for additional follow-up and referral for women following HDP. More research on the benefits and risks of such an approach is needed.